O ageism e os maus-tratos contra a pessoa idosa - Vergueiro, Maria Emília de Clara (2010)
The purpose of this study was to investigate if social discrimination based in age (Ageism) is related with risk of elder abuse, mistreatment and /or negligence. 54 subjects participated in this study and were distributed by two groups: old people (N=33) and care providers/punctual assistance of eldery (N=21), to whom were administered, besides a socio-demographic interview, an elder abuse evidence instrument (QEEA – Questions to Elicit Elder Abuse) and Ageism related instruments Ageism Survey in eldery) and ARPI – Relacionamento com Pessoas Idosas - in care providers. The results, based on the general indices of these questionnaires, don’t find any correlations between the two phenomena. However, a deeper analysis of the ageism items allows to confirm the existence of correlations between some of these items and the elder abuse evidence.